Correlation between Food Schemes and Children Nutrient Status at the Toddler’s Age - Tri Ratnaningsih; Indah Lestari (Institute of Advanced Engineering and Science, 2016)
The nutrient in the meal is very important, especially for the children at the toddler’s age. The aim of this research was to know the correlation between the food schemes with the children nutrient status at the toddler’s age (1-3 years). The research design was cross sectional. The population for this research was all of the mothers and the children at the toddler’s age (1-3 years). The sample was taken using purposive sampling method. Many respondents served in appropriate meal to their children. Many children suffered poor nutrition status.